Highlights from the 2022 ASCO gastrointestinal cancer symposium: An overview by the EORTC gastrointestinal tract cancer group - Sclafani, Francesco; Fontana, Elisa; Wyrwicz, Lucjan; Wagner, Anna Dorothea; Valle, Juan W; Smyth, Elizabeth; Peeters, Mark; Obermannova, Radka; Neuzillet, Cindy; Lutz, Manfred P; Koessler, Thibaud; Ben-Aharon, Irit; et al. (Clinical colorectal cancer, 2022)
Recently, we have witnessed impressive diagnostic and therapeutic changes for gastrointestinal cancer patients. New challenges brought by the COVID-19 pandemic have led us to re-evaluate our work priorities. Thanks to the commendable resilience of both investigators and patients, however, clinical research never stopped. In addition to conducting cutting-edge research and serving patients' needs, as EORTC Gastrointestinal Tract Cancer Group, we are committed to pursuing educational initiatives beneficial to the entire European oncology community and beyond. In this regard, we have been providing critical discussions of new data from major international meetings. In this article, we discuss results of important selected studies presented at the 2022 ASCO Gastrointestinal Cancer Symposium, putting them in perspectives and highlighting potential implications for routine practice. With the number of in-person attendees and practice-changing/informing trials presented, this meeting represented a milestone in the return to normality as well as in the fight against cancer.
Keywords: Gastrointestinal Neoplasms; Esophago-gastric cancers; lidé; Medical Oncology; Hepato-pancreatico-biliary cancers; Pandemics; Colorectal cancers; COVID-19; pandemie; gastrointestinální nádory; Clinical trials; lékařská onkologie; Humans; Meeting